Umbilical cord mesenchymal stem cells and their secretome in peripheral nerve regeneration: a narrative review promising therapeutic strategy - Tito Sumarwoto; Seti Aji Hadinoto; Romaniyanto; Sholahudin Rhatomy; Pamudji Utomo; Mujaddid Idulhaq; Asep Santoso; Heri Suroto (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
The injuries of peripheral nerves remain a substantial clinical challenge because of their limited regenerative capacity, the complexity of nerve repair, and limitations of current treatment strategies. Umbilical cord mesenchymal stem cells (UC-MSCs) and their secretome have shown promise as regenerative treatments due to their distinct biological characteristics. This review explores the possibility of UC-MSCs and their secretome in promoting peripheral nerve regeneration, by their action mechanisms, therapeutic applications, and current preclinical - clinical evidence. UC-MSCs have proven to be capable of support Wallerian degeneration, improving axonal growth, reducing inflammation, and improving functional recovery in both animal models and early clinical studies. Their secretome has been shown to promote neuroprotection and functional repair, avoiding the risks of receiving a direct stem cell transplant. Challenges remain in standardizing UC-MSC-based therapies, ensuring long-term safety, and enhancing delivery strategies. Further clinical trials are needed to determine the efficacy, safety, and scalability of UC-MSC therapies for widespread clinical use. UC-MSCs and their secretome provide a unique, cell-free and cell-based strategy to peripheral nerve regeneration. Future advancements in biomaterial integration, gene editing, and personalized medicine will be essential to implementing these treatments in clinical settings.